Acoustic analysis of wolf howls recorded in Apennine areas with different vegetation covers. Issue 5 (2nd September 2020) - Russo, Claudia; Cecchi, Francesca; Zaccaroni, Marco; Facchini, Claudia; Bongi, Paolo
Abstract : In animal communication, acoustic signals can be used to census individuals as well as groups of individuals of the same species. The wolf ( Canis lupus ) is a protected species in Europe, and the study of its vocalizations may furnish information about its spatial distribution, reproductive success, and social behaviour. This study was conducted in seven locations of the Tuscan Apennines over 2 years. Seven different free-ranging wolf-packs, from different environmental habitats, were recorded. The minimum wolf number of each pack was ascertained along with the presence of pups. Different acoustic characteristics were found among packs, confirming that the group-specific vocal signature is a useful method to recognize packs in the wild. Howls were also analysed in relation to different environmental characteristics, and different frequencies were found to correlate open/closed habitats, so environmental variables should be included in sound analysis models to recognise individual packs.